Prevalence and risk factors for depression and anxiety in patients with nasolacrimal duct obstruction - Guo, Yining; Wu, Defu; Jin, Yu; Tian, Yanjie; Li, Xuemin (Frontiers in Psychiatry, 2023)
Objective: To investigate the prevalence and risk factors for depression and anxiety in patients with nasolacrimal duct obstruction (NLDO).: We conducted a telephone-based survey of patients with NLDO who underwent dacryocystorhinostomy (DCR) at the Department of Ophthalmology of Peking University Third Hospital in China between January 2016 and January 2021. Depression and anxiety were assessed with the PHQ-9 (range 0-25) and STAI (range 20-80) scales. PHQ-9 ≥5 and STAI ≥55 were considered clinically significant. Logistic regression and linear regression were performed to determine the factors related to depression and anxiety.Results: Of 565 patients approached, 344 (60.9%) completed the survey. A total of 13.1% of patients had mildsevere depression and 63.4% had severe anxiety. Univariate logistic regression revealed that hypertension, dry eye, and cataract were associated with mild to severe depression (P = 0.018, 0.045, 0.035, respectively). Dry eye was associated with severe anxiety (P = 0.007). Univariate linear regression revealed that male and income levels were significantly negatively correlated with PHQ-9 scores (P = 0.011, 0.010, respectively). Hypertension and dry eye were significantly positively correlated with PHQ-9 scores (P = 0.030, P<0.001, respectively).Male, income levels, and educational levels were significantly negatively correlated with STAI scores (P=0.022, P<0.001, P=0.005 respectively). Dry eye was significantly positively correlated with STAI scores (P<0.001).Prevalence of depression and anxiety disorders was relatively high among NLDO patients. Our results demonstrate the importance of depression and anxiety screening and psychosocial support for patients with NLDO, which can improve their quality of life and compliance with medical appointments.